Home Bias in Top Economics Journals - Dirk Bethmann; Felix Bransch; Michael Kvasnicka; Abdolkarim Sadrieh (Institute of Labor Economics (IZA), 2023)
Two of the top economics journals have institutional ties to a specific university, the Quarterly Journal of Economics (QJE) to Harvard University and the Journal of Political Economy (JPE) to the University of Chicago. Researchers from Harvard, but also nearby Massachusetts Institute of Technology (MIT), and from Chicago (co-)author a disproportionate share of articles in their respective home journal. Such home ties and publication bias may harm, but also benefit, article quality. We study this question in a difference-in-differences framework, using data on both current and past author affiliations and cumulative citation counts for articles published between 1995 and 2015 in the QJE, JPE, and American Economic Review (AER), which serves as a benchmark. We find that median article quality is lower in the QJE if authors have ties to Harvard and/or MIT than if authors are from other top-10 universities, but higher in the JPE if authors have ties to Chicago. We also find that home ties matter for the odds of journals to publish highly influential and low impact papers. Again, the JPE appears to benefit, if anything, from its home ties, while the QJE does not.
Keywords: A11; I2; J24; 330; publishing process; institutional ties; citations; home bias